A case study of the efficiency of space planning modifications of three residences to accomodate home-based small scale foodservice business - Bartolome, Judy Rose C.; Buencamino, Lorena M. (2007)
The study concentrated on the efficiency of the space planning modifications that three residences have undergone to accommodate home-based, small scale food service businesses in the Philippine setting. A case study approach that applied purposive data sampling was adapted to obtain and analyze qualitative data with the use of observations, interview, and questionnaire sheets. Data analysis employed descriptive and analytical methods of study. The forty eight respondents of the study included home and business owners, family members, household staff, and business employees in the three residences and businesses. Results identified the activities performed in the home and business spaces such as daily chores and self-sustaining activities, personal routine and business operating activities. It was discovered that the space plans of all three subjects were reasonably efficient based on the business profit and user response but rather inefficient in terms of specialized standards and energy output. Typical issues and problems drawn out from the study were the lack of business atmosphere, conflicting function of areas, lack of privacy, lack of storage and work space, and physical isolation. Home-users and workers tend to make do and be content with the present state of space as long as it serves its main purpose of providing shelter, protection, and business venue. The end result was a recommendation which include the reevaluation of the space plan with more effective space programming techniques. The study also suggests considering standard requirements of space planning to harmoniously incorporate home based small-scale food service business. Lastly, keep the private home space and public business space separate, if possible, or maintain order and organization of space between the two.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Space (Architecture).; Dwellings -- Remodelling